The Importance of the Approach to Use of the Surrounding Environment in Class 1 Social Sciences Learning: Reviewing Its Effectiveness in the Context of the Free Curriculum - Aulia Marhamatun Nufus (Penerbit Hellow Pustaka, 2024)
Learning Social Sciences (Social Sciences) at the elementary school level play an important role in helping students develop initial understanding of the surrounding social, cultural, and geographical environment. In improving the quality of social studies learning in class one, many educators adopt an approach that utilizes the environment as a learning resource. This approach is expected to provide a more realistic and in -depth learning experience because students are directly involved in the reality of their environment. Therefore, this approach not only increases understanding but also encourages students to develop observation, analysis, and problem solving skills. However, the emergence of an independent curriculum that emphasizes situational learning and local wisdom requires critical evaluation of the effectiveness of this approach in a new context. The research method uses qualitative research which is based on the analysis of the problem which is then described through the idea of ​​researchers.